CWTS - Certified Wireless Technology Specialist Exam PWO-071 - Bartz, Robert J. (John Wiley & Sons, Incorporated, 2012)
Pass the CWTS exam with the help of this fully updated official guide Completely updated to cover the latest Certified Wireless Technology Specialist exam, this best-selling guide is the only Official Study Guide for the popular wireless certification. This foundation-level certification is in high demand for wireless networking professionals, and you can master all the exam topics with this Official guide. It covers all the exam objectives and helps you study with hands-on exercises, chapter review questions, an objective map, a pre-assessment test, and additional study tools on the companion website. The only official study guide endorsed by CWNP Thoroughly covers all exam objectives, including Wi-Fi Technology, Standards, and Certifications; Hardware and Software; Radio Frequency (RF) Fundamentals; Site Surveying and Installation; Applications, Support, and Troubleshooting; and Security & Compliance Includes hands-on exercises and real-world scenarios to increase understanding Study aids include review questions, glossary, objective map, sample tests, and electronic flashcards CWTS: Certified Wireless Technology Specialist Official Study Guide, 2nd Edition is the study buddy that will enhance your chances for exam success. Note: CD-ROM materials for eBook purchases can be downloaded from http://booksupport.wiley.com
Description based on publisher supplied metadata and other sources
Keywords: Telecommunications engineers -- Certification -- Study guides; Wireless LANs -- Examinations -- Study guides